Chemical analyses of manganese nodule samples from the ESSA-NOAA AMC-11-67 cruise over the Blake Plateau - R W Wittkopp; J D Stephens (PANGAEA, 2023)
For assessing their desulfuration and mineral potential, manganese rich concretions were selected from the stations of the AMC-11-67 cruise performed by ESSA (NOAA) in October 1967 and analysed by the Kennecott Copper Corporation.